Early Bilingual Education in a Monolingual Environment. Showcasing Polish Families - Romanowski, Piotr (Complutense Journal of English Studies, 2018)
The overriding aim of the article is to present, evaluate and discuss the effectiveness of early bilingual education in a monolingual environment, such as Poland. As opposed to situations where parents use two languages due to their different nationalities and backgrounds or instances of employing foreign nannies to address children in another language (usually their own L1), this paper will focus on a controversial issue of using a foreign language (L2) by a parent and speaking it to a child in a natural way. The purpose of the theoretical section is to depict the role of parents, the possible strategies used in raising children bilingually as well as potential problems to be encountered in the process. The subsequent empirical part outlines the results of analysed case studies collected from 22 Polish families who have successfully employed such a model of language learning and communication with their children.